(untitled) (Construction Economics and Building, 2018)
Skilled labour shortage in construction industry is a major challenge in South Africa. Therefore, the objective of the study is to assess the factors that cause skilled labour shortage, its consequent effects on the construction industries and how the scenario can be improved. The study was conducted by considering construction industry in the Eastern Cape of South Africa and using a survey research method and conceptual System Dynamics (SD) modelling. Findings reveals that investment, wage challenges, talent management, work environment, training, experience, and Government policy are the important challenges for the skilled labour shortage. Inadequacy of skilled labour considerably impacts the quality of work, productivity, and scheduling. The causal loop diagrams show that enhancement in investment in the labour wages will strengthen the availability of skilled labourers leading to higher productivity, and vice versa. Talent management based on appropriate recruitment and retention policy, staff development programmes and investment in these aspects will augment the skilled labour pool. Also, a better work environment through a policy of health and safety, investment in working condition and supported by Government policy will reduce the attrition of the labourer because of job dissatisfaction, which consequently will reduce the skilled labour shortage in the industry.